Genetic Diversity in Three Sinipercine Fishes Based on Mitochondrial D-Loop and COX1 Sequences - Minghui Lin; Xu-Fang Liang; Ke Lu; Ming Zeng; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Fishes)
Mandarin fish (Siniperca chuatsi), golden mandarin fish (Siniperca scherzeri), and Coreoperca whiteheadi are three important aquaculture species in China facing several threats to their production. Genetic diversity was assessed by sequencing the mitochondrial D-loop and cox1 regions in 207 individuals across nine populations. The genetic diversity analysis, based on the concatenated sequences, revealed that the total haplotype diversity was high across all sinipercine fish populations. Population differentiation analysis revealed that most genetic variation was within populations: 74.5% in S. chuatsi (p < 0.001) and 83.0% in S. scherzeri (p < 0.001). All five S. chuatsi populations showed moderate and significant genetic differentiation, and moderate genetic differentiation was observed between the Beijiang and Wujiang populations in S. scherzeri. Phylogenetic and nested clade analysis indicated that artificially bred and wild S. chuatsi populations shared haplotypes, and close phylogenetic relationships were observed between the Beijiang and Dongjiang populations in S. scherzeri. These findings could be useful for the conservation management, artificial breeding, and hybridization of these three sinipercine fish species.